TRADISI PANGANTAN NGINDRING PADA MASYARAKAT SUMBAWA DI KECAMATAN MOYO HILIR KABUPATEN SUMBAWA - Satriani, Ani; Lestari, Dinna Eka Graha (Universitas Negeri Semarang, 2020)
This research attempts to answer several problems which include: 1) How is the proposal for the Pangantan Ngindring tradition at the traditional wedding ceremony of the Sumbawa Nation in Moyo Hilir District, Sumbawa Regency, 2) The function of the Pangantan Ngindring Tradition in the traditional wedding ceremony of the Sumbawa people in Moyo Hilir District in the Regency Sumbawa, 3) How is the continuity of the Pangantan Ngindring tradition in the midst of community life in Moyo Hilir District. The purpose of this study is to describe the origin of the Pangantan Ngindring tradition at the traditional wedding ceremony of the Sumbawa Tribe in Moyo Hilir District, describe and analyze the function of Pangantan Ngindring in the traditional Sumbawa ethnic wedding ceremony in Moyo Hilir District and describe and analyze the continuity of the Pangantan Ngindring tradition in the midst of life. the people of Moyo Hilir sub-district. This research uses a qualitative research approach and is included in the type of descriptive research. The data collection methods used in this study are: observation, interviews, and documentation. The data analysis used is descriptive analysis which will provide a continuous picture from beginning to end in order to obtain a description of the Pangantan Ngindring tradition. In this study, checking the validity of the data using techniques: observation persistence, mode triangulation and theory triangulation, adequacy of references. This study found that the origin of the Pangantan Ngindring tradition was from the habits of the Sumbawa people, especially those in Moyo Hilir District, to match their children with family or relatives. Therefore, neither party knows each other. In order to avoid unwanted things in married life, such as quarrels or divorces, the Pangantan Ngindring tradition was held. Tujuan dari penelitian ini adalah untuk mendreskripsikan asal usul tradisi Pangantan Ngindring pada upacara perkawinan adat, mendeskripsikan dan menganalisis fungsi Pangantan Ngindring pada upacara perkawinan adat serta mendeskripsikan dan menganalisis kelangsungan tradisi Pangantan Ngindring ditengah kehidupan masyarakat kecamatan Moyo Hilir. Penelitian ini menggunakan pendekatan penelitian kualitatif dan termasuk dalam jenis penelitian deskriptif. Adapun metode pengumpulan data yang digunakan dalam penelitian ini yaitu: observasi, wawancara, dan dokumentasi. Analisis data yang digunakan adalah analisis deskriptif. Dalam penelitian ini pengecekan keabsahan data dengan menggunakan tehnik: ketekunan pengamatan, triangulasi mode dan triangulasi teori, kecukupan referensi. Penelitian ini mendapat hasil bahwa asal usul tradisi Pangantan Ngindring adalah bermula dari kebiasaan masyarakat Sumbawa khususnya masyarakat yang berada di Kecamatan Moyo Hilir untuk menjodohkan anaknya dengan keluarga atau kerabat. Oleh karena itu kedua belah pihak tidak ada yang saling mengenal satu sama lain. Guna menghindari hal hal yang tidak diinginkan dalam kehidupan berumah tangga, misalnya seperti pertengkaran maupun perceraian, maka diadakanlah tradisi Pangantan Ngindring.